FINDING SHORTEST PATH FOR DYNAMIC PUTTING PROBLEM USING ANT COLONY OPTIMISATION - Nor Akmal, Abdul Aziz (Universiti malaysia sarawak (UNIMAS), 2005)
This study aims to find the shortest path for free plotting nodes. Am Colony Optimisation (ACO) was chosen to solve this problem. Specifically. this thesis is intended to develop a system that can display the shortest path by the used of two algorithm in ACO which were Ant System (AS) and Ant Colony System (ACS). Besides, this thesis also aimed to compare both algorithms used in the system, based on their speed to generate the shortest path. The speeds were measured in seconds for each problem set. As a conclusion, this project had proved the fact that ACS generates the solution faster than AS. Lastly, this project also includes several recommendations for future work as an extension of this project